Brides in family or in institute: Dowry between customs, symbols and rituals in Southern Italy (18th-19th centuries) - Carbone, Angela (Études sur la Région Méditerranéenne, 2020)
This paper, mainly based on unpublished archival sources, focuses on marriage customs in Terra di Bari between the 18th and 19th centuries. Daughters in marriageable age and future brides become protagonists of a period of their life, prior to the celebration of marriage, in which family strategies, dotal systems, symbols and rituals were strongly conditioned by social belonging and the juridical status of the girl. The focus is, in fact, not only on the legitimate daughters “in the family”, but also on the orphans and institutionalized foundlings for whom the institutes also took on the role of their “welfare family” as regarding marriage.